Assessing the performance of cashless society innovations - NG, Dennis Chong Meng (Institutional Knowledge at Singapore Management University, 2019)
Payments research is essential in supporting the move towards a cashless society. This dissertation uses mixed methods, a field experiment and comparative analysis to propose a payments framework, assess incentive effectiveness, and investigate the role of habits and challenges related to adoption. Essay 1 examines whether customers carry one payment instrument over their lifetime. By analysing payments through a customer relationship management and life cycle lens, the research brings a fresh perspective on how payment providers may need to offer different payment options across the customer life cycle if they wish to maximise customer lifetime value through a lifecycle framework of electronic payments choice. The essay also finds that payment choice is affected by regulations, parental choices, and the financial, social and psychological needs of consumers, which can be used as a basis for creating new products that are relevant for each life stage. Essay 2 assesses the effectiveness of incentives and the role of habits on cashless payment adoption at the point-of-sale. Using a field experiment, preliminary results obtained seem to confirm the effectiveness of financial incentives on electronic payment adoption. However, behaviour change falls below control levels after the incentive is stopped. Furthermore, habits seem to hinder cashless payment adoption when cash has been the predominant method of payment. Five key takeaways are provided for greater adoption success. Essay 3 studies the challenges of introducing high-technology payment applications into low-technology adoption settings which is common when countries embark on a cashless payment journey. The study uses a comparative analysis approach to analyse the success of the Singapore Smart Nation E-Payment Initiative by comparing its success thus far with M-Pesa, a successful retail cashless payment project in Kenya. The comparative analysis approach allows for a deeper analysis of government policy, banking infrastructure and the socio-economic development on the ground. The adoption of innovation and ground-level consumer behaviour factors are also taken into consideration. Barriers to cashless adoption are discussed and solutions offered for a smoother transition to a cashless society. The findings from Essay 1 will provide practitioners a deeper understanding of what affects payment choice at different stages of a customer’s life cycle. It also highlights the critical role of regulations in determining the potential market, which also highlights the need for practitioners to engage the regulator continuously so that regulations are updated and appropriate. New perspectives on managing business portfolios arising from the need to maximise customer lifetime value are also offered. Essay 2 findings can provide clear guidance on how incentives can be better used to speed up cashless payment adoption. It also highlights that habits may need to be better understood and managed to reduce their negative impact on cashless payment adoption both from a research and also a practitioner point-of-view. Essay 3 provides guidance from a macro-perspective on the critical factors required for cashless payment adoption success. Contrary to conventional wisdom, developed countries may encounter unique challenges to cashless payment adoption as it relates to high-technology payment application to low-technology payment deployment settings. The essay highlights previously unresearched areas on unique barriers that developed countries may face. Together, these essays provide insights to academics to further their study into payments research from a multi-disciplinary perspective. For policy makers and practitioners, these essays will help guide decision making on what works in the field towards cashless payment adoption.